PENGARUH BUSINESS PROCESS REENGINEERING TERHADAP BUSINESS PROCESS PERFORMANCE PADA HOTEL BUDGET DI SURABAYA - Adrie Oktavio (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2017)
In such a tight business competition climate, the management of budget hotel is required to think of innovative and sustainable business strategies in order to survive and compete with other hotels in the long term. Business strategy in question here is to make an innovation that aims to improve Business Process Performance. For that, the management of budget hotel has time to start changing the mindset in running the hotel operations, more process-oriented, so that required a fairly fundamental change in completing a task or job. Completion of a task or job in a business process can be done through a reengineering on a company's business process called Business Process Reengineering (BPR). This study uses correlational research method that aims to test the magnitude of the influence of BPR on Business Process Performance. The data used in the test is obtained from the spread of questionnaires at budget hotels in Surabaya which the results can be concluded that the BPR has a positive and significant impact on Business Process Performance